2011
DOI: 10.1159/000329871
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Computed Tomography Quantitation of Emphysema Is Correlated with Selected Lung Function Values in Stable COPD

Abstract: Background: The literature shows conflicting results when high-resolution computed tomography (HRCT) scores of emphysema were correlated with different indices of airflow obstruction. Objectives: We correlated HRCT scores of emphysema with different indices of airflow obstruction. Methods: We performed HRCT of the chest in 59 patients, all smokers or ex-smokers, with stable chronic obstructive pulmonary disease of different severity [GOLD stages I–IV; mean age ± SD 67.8 ± 7.3 years; pack/years 51.0 ± 34.6; per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 65 publications
4
25
0
Order By: Relevance
“…As such, a significant association between emphysema grade and both IC/TLC and DLCO was found in the total study population. This is consistent with previous studies, which have shown associations between emphysema and hyperinflation, as well as DLCO 17,39. Furthermore, a significant association between emphysema grade and FEV 1 was seen in both the total study population and the 0–1 comorbidity subgroup, which is consistent with previous studies, although these have been of variable strength 39,40.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As such, a significant association between emphysema grade and both IC/TLC and DLCO was found in the total study population. This is consistent with previous studies, which have shown associations between emphysema and hyperinflation, as well as DLCO 17,39. Furthermore, a significant association between emphysema grade and FEV 1 was seen in both the total study population and the 0–1 comorbidity subgroup, which is consistent with previous studies, although these have been of variable strength 39,40.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous studies, which have shown associations between emphysema and hyperinflation, as well as DLCO 17,39. Furthermore, a significant association between emphysema grade and FEV 1 was seen in both the total study population and the 0–1 comorbidity subgroup, which is consistent with previous studies, although these have been of variable strength 39,40. Moreover, no association was found between TLC and emphysema grade, which is supported by previous findings 41.…”
Section: Discussionsupporting
confidence: 92%
“…Prior literature has indicated that emphysema – particularly panlobular emphysema – is only modestly associated with smoking, as shown on autopsy (13), on CT scan in COPD patients (17, 56), and in the current cohort (57). Nonetheless, compared to strong and consistent associations observed among smokers, findings among never-smokers were modest and did not attain statistical significance, although neither did the statistical test for effect modification by smoking history.…”
Section: Discussionmentioning
confidence: 75%
“…69 Regardless, given that lung cancer screening is now recommended in smokers, 70 emphysema on CT may be increasingly available for clinical decision-making. We did not evaluate DLCO, which associates with dyspnea 71 and correlates modestly with emphysema on CT. 72 Bronchoprovocation, exercise testing and plethysmography were not performed. A measure of anemia was not available, however due to physiologic adaptations, anemia must be severe in order to cause dyspnea in otherwise healthy adults, such as those enrolled in MESA.…”
Section: Discussionmentioning
confidence: 99%